VIRTUAL MULTISLICE-CT-BRONCHOSCOPY AS A DIAGNOSTIC TOOL IN PATIENTS WITH BRONCHIAL TUMORS - P. M. Kotlyarov; N. I. Sergeev; V. A. Rebrikova; О. V. Tatarnikova (Сибирский онкологический журнал)
Purpose: to study the role of virtual multislice-CT-bronchoscopy in the detection of bronchial tumors and assessment of bronchial tumor extension. Material and methods. Findings of the virtual multislice-CTbronchoscopy were analyzed in 61 patients with primary and secondary bronchial tumors. Virtual multislice-CTbronchoscopy was performed using the AquilionONE (320-slice) CT scanner. Results. Virtual bronchoscopy revealed 3 types of bronchial involvement: peribronchial, intrabronchial and mixed tumor infiltrations. The virtual fly through bronchoscopy was used to assess the macrostructure and tumor margins in patients with intrabronchial tumor growth. Broad-based polypoid masses causing the obstructing narrowing of the bronchus were visualized inside the bronchial lumen. The narrowing of the bronchial lumen and no visualization of the cartilaginous structures (the bronchus turned into the deformed tubular structure) were the signs of infiltration of the main bronchi and the trachea. In patients with lung and hilar lymph node metastases, infiltration of segmental and lobar bronchi led to the impaired ventilation of the affected segments or lobes of the lungs, thus resulting in the development of atelectasis. In patients with benign tumors, the lesion was characterized by the regular shape, smooth surface and homogeneous internal structure, as well as the absence of infiltration of the bronchial wall. Conclusion. Virtual multislice-CT-bronchoscopy with multiplanar and three dimensional reconstruction is a reliable noninvasive method for accurate diagnosis of bronchial involvement and the differential diagnosis between extrinsic pressure on the bronchial tree and bronchial tumor.